FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN SEBELUM DAN SELAMA PANDEMI COVID-19 - Brenda, Stephani; Yanti, Yanti (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to obtain empirical evidence of investment opportunities, profitability, leverage, and firm size effects on dividend policy before and during COVID-19 pandemic. The population in this study are manufacturing companies listed on IDX during the years 2019-2020 consisting of 42 samples. Data the year 2019 represent conditions before the pandemic, whereas data the year 2020 represent conditions during pandemic. Hypothesis of this study are tested with regression analysis and the Wilcoxon. The results of the study show that before the the pandemic, leverage had a significant effect on dividend policy, on the other hand, investment opportunity, profitability, and firm size had no significant effect on dividend policy. During the pandemic investment opportunity, profitability, and leverage had a significant effect on dividend policy, in contrast, firm size had no significant effect on dividend policy.